Ilaw ng Ibang Tahanan: Transnational Mothering Practices of Overseas Filipina Domestic Workers during the COVID-19 Pandemic - Ramirez, Arvin John C. (Animo Repository, 2024)
Filipino mothers traditionally serve as primary caregivers and, at times, as the main breadwinners for their families. With limited opportunities in the Philippines, many seek employment abroad, leaving their children behind. Data from the Philippine Statistics Authority indicated that female Overseas Filipino Workers (OFWs) often engage in elementary jobs, including domestic work and caregiving. The COVID-19 pandemic added a challenge in fulfilling their maternal needs since health and safety have become everyone’s priority. This study investigates the transnational mothering practices of overseas Filipina domestic workers during the pandemic and how these practices differ from those before the health crisis. Through online interviews with five OFWs, the research found that despite the geographical distance, these workers find reassurance in knowing their relatives care for their children in the Philippines. Also, effective communication through social media emerged as a crucial element in their caregiving, allowing them to remind their children to stay safe during the pandemic. Moreover, the study highlighted the financial support provided by OFWs through remittances, which contributed to the personal and educational needs of their children. This paper introduces new possibilities for scholarships related to transnational mothering and experiences of the Overseas Filipino Workers during the COVID-19 pandemic, especially for Filipino mothers. It also underscores the challenges and resilience of Filipino domestic workers in maintaining their maternal roles despite physical separation from their families as the ilaw ng tahanan while being the ilaw ng ibang tahanan overseas.